The Role of Human Resources Analytics in Talent Management to Enhance Organizational Resilience and Achieve Competitive Advantage: An Applied Study at Mansour Pharmaceutical and Medical Supplies Company - Yousif Riyadh Mhmood; Rawad Fadhil Abed Alabboodi; Alyaa Hussein Mohmmed Ali Alesa (International Journal on Economics, Finance and Sustainable Development, 2026)
The research aims to study role Analysis Resources Humanity in administration talents to promote Flexibility Organizational and investigation Feature competitiveness, with the focus on a company Al-Mansur For industries pharmaceutical and supplies Medical As an example My application. In shadow environment Business variable quickly, I became companies Need to tools minute To support Taking Decisions strategy Related With resources Humanity, Guarantee to exploit talents In a way effective In what Serves Goals The organization. Use. Search Curriculum Descriptive Analytical, And it was collected Data from during Surveys Interviews with employees My managers Resources Humanity, In addition to review Records Analysis Resources Humanity Available in The company showed Results that Use Analysis Resources Humanity Contributes In a way direct in to improve Operations administration Talents, and increase capacity Company on Adaptation with Changes Organizational, and strengthening Innovation, and investigation feature competitive clear in The market is finished. Search to that to merge Analysis in administration talents It represents tool strategy Effective To promote Flexibility Organizational, He recommends Developing Abilities Analysis I have difference Resources Humanity And adopt Organized information Advanced To support Taking The decision. As well. It indicates Search to importance Expansion in Use Data analytical To expect needs employees Future and improving Strategies Keeping With talents.